2022
DOI: 10.3389/fonc.2022.977119
|View full text |Cite
|
Sign up to set email alerts
|

An easy-to-use nomogram predicting overall survival of adult acute lymphoblastic leukemia

Abstract: Adult acute lymphoblastic leukemia (ALL) is heterogeneous both biologically and clinically. The outcomes of ALL have been improved with the application of children-like regimens and novel agents including immune therapy in young adults. The refractory to therapy and relapse of ALL have occurred in most adult cases. Factors affecting the prognosis of ALL include age and white blood cell (WBC) count at diagnosis. The clinical implications of genetic biomarkers, including chromosome translocation and gene mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Previous attempts to develop an integrated prognostic model in adult ALL have clearly demonstrated the superiority of this approach compared with using individual risk factors. 1 , 2 However, neither study was able to validate the model using external cohorts and neither considered EOI MRD in the modeling process. Although both studies identified a HR group that had very poor outcome of OS <25% at 2 years, the outcome of the patients in the SR group was also relatively poor at ∼50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts to develop an integrated prognostic model in adult ALL have clearly demonstrated the superiority of this approach compared with using individual risk factors. 1 , 2 However, neither study was able to validate the model using external cohorts and neither considered EOI MRD in the modeling process. Although both studies identified a HR group that had very poor outcome of OS <25% at 2 years, the outcome of the patients in the SR group was also relatively poor at ∼50%.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 previous studies have developed integrated prognostic models in adult ALL. 1 , 2 Neither study considered MRD, and both lacked external validation cohorts. We have recently developed and validated an integrated prognostic index (PI), called UKALL-PI, using childhood, adolescent, and young adult patient cohorts that leverages the power of continuous data and provides a more flexible mechanism for defining risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have been mechanistically associated with chemoresistance and are enriched at relapse 4,[8][9][10][11][12] . CREBBP mutations have also been described as an adverse prognostic factor in ALL, acute myeloid leukaemia (AML) and follicular lymphoma [13][14][15] . CREBBP is a large protein with histone acetyltransferase (HAT) enzymatic activity alongside protein scaffolding function mediated through multiple protein-protein interaction domains, including a bromodomain responsible for binding acetylated lysine residues.…”
Section: Introductionmentioning
confidence: 99%